1983
DOI: 10.1016/0014-5793(83)80573-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate shuttle ‐ transport of energy from mitochondria to cytosol

Abstract: Brown‐adipose tissue mitochondria of hamster and rat contain phosphoenolpyruvate carboxykinase (EC 4.1.1.32). In the presence of ketoglutarate and malate, phosphoenolpyruvate is formed and exported forms mitochondria. Phosphoenolpyruvate formation is inhibited by 1,2,3‐benzenetricarboxylate. It is proposed that phosphoenolpyruvate carboxykinase together with pyruvate carboxylase and pyruvate kinase forms a phosphoenolpyruvate shuttle through which energy produced by the Krebs cycle in mitochondria may be expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The role of mitochondrial PEPCK in tissues that do not exhibit gluconeogenesis remains to be defined. Possibilities include the regulation of intramitochondrial concentrations of 4-carbon citric acid cycle intermediates [14] and export of energy to the cytosol [5].…”
Section: Discussionmentioning
confidence: 99%
“…The role of mitochondrial PEPCK in tissues that do not exhibit gluconeogenesis remains to be defined. Possibilities include the regulation of intramitochondrial concentrations of 4-carbon citric acid cycle intermediates [14] and export of energy to the cytosol [5].…”
Section: Discussionmentioning
confidence: 99%
“…Drahota et al identified very high specific activities of PEPCK-M in brown adipose [40]. In addition, they reported high rates of PEP export from mitochondria supplied with malate and alpha-ketoglutarate.…”
Section: Sensing Tca Cycle Fluxmentioning
confidence: 99%
“…The latter reaction would increase the adenylate charge and could be a part of "pyruvate cycling," the rate of which can exceed by severalfold the rate of flux through the citric acid cycle and the synthesis of glucose (18). Rather than being an energy-wasting, futile cycle, such cycling of P-enolpyruvate and pyruvate may be a mechanism for transferring phosphorylation potential from mitochondria to cytosol (19).…”
Section: Table II Specific Activities Of A-scs and G-scs Inmentioning
confidence: 99%